Technical and economic optimization of expander-based small-scale natural gas liquefaction processes with absorption precooling cycle. (15th January 2020) - Zhang, Jinrui; Meerman, Hans; Benders, René; Faaij, André
Abstract: The objective of this study is to investigate potential technical and economic performance improvement for expander-based natural gas liquefaction processes in small-scale applications. Four expander-based processes were optimized and compared in this study, including conventional single nitrogen expansion process without (SN) and with ammonia absorption precooling (SNA), and single methane expansion process without (SM) and with ammonia absorption precooling (SMA). A two-phase expander is utilized in the methane expansion process to enable liquid generation at the expander outlet. The optimization was done with two objective functions: minimization of specific energy consumption and minimization of production cost. The energy and cost analyses were performed for the four processes by comparing optimization results. Lastly, exergy losses in the main equipment were analyzed. The results show that the ammonia precooling cycle reduces energy consumption and production cost by 26–35% and 13–17%, respectively. The single methane process with precooling is the most promising process, which has 28–48% lower energy consumption and 13–43% lower production cost compared to those of the other three processes. Results also indicate that the best techno-economic performance is obtained with objective of minimizing production cost and not with the commonly used energy-related objective. Highlights: Four expander-based processes are numerical optimized for small-scale LNG plants. Ammonia absorption precooling cycle can be powered by waste heat from gas turbine. Ammonia precooling cycle improves techno-economic performance of the process. Methane processes have better techno-economic performance than nitrogen processes. Minimizing energy consumption do not lead to minimum production cost.